Giant Cystic Lymphohemangioma of Retroperitoneal Pelvic with Extension to Inguinal Canal and Scrotum - V.K. Litovka; I.P. Zhurilo; S.V. Vesely; K.V. Latyshov (Zaslavsky O.Yu., 2012)
The clinical case of giant retroperitoneal cystic lymphohemangioma with extension to the inguinal canal and scrotum was given. After surgical treatment the patient recovered